Advances in the Anticancer Value of the Ursolic Acid Through Nanodelivery - Manayi, Azadeh; Nikan, Marjan; Nobakht-Haghighi, Navid; Abdollahi, Mohammad (Bentham Science Publ Ltd, 2018)
Ursolic acid, a natural pentacyclic triterpenoid is commonly found in plants and foods with promising biological and pharmacological activities. The compound has been under the attention of researchers due to its considerable anticancer effects through suppression of differentiation, angiogenesis, invasion, and metastasis of tumor cells via different pathways with low toxicity. Bioavailability of ursolic acid is poor due to poor solubility of the compound in water. Low bioavailability and short plasma half-life of ursolic acid along with non-specific distribution in the body are considered as impediments in the therapeutic development of the compound. Nano-drug delivery systems may improve the pharmacokinetic, bioavailability, and therapeutic activity of some medicines. The present review has focused on recent developments regarding nano-drug delivery systems of ursolic acid in cancer therapy.
Keywords: Bioavailability; cancer; nanomedicine; natural compounds; ursolic acid; review